2018
DOI: 10.1139/apnm-2017-0594
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine supplementation does not improve muscle function during recovery from resistance exercise

Abstract: The purpose of this study was to investigate the effects of l-arginine supplementation on muscle recovery after a single session of high-intensity resistance exercise (RE). Twenty healthy young adult participants (22.8 ± 3.4 years old) were assigned to 1 of 2 groups (N = 10 per group): a placebo-supplement group or an l-arginine-supplement group. The groups completed a session of high-intensity RE (0 h) and 3 subsequent fatigue test sessions (at 24, 48, and 72 h postexercise) to assess the time course of muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…For instance, arginine supplementation has been tested in athletes, as vasodilation favors muscle perfusion and nutrient/oxygen delivery during exercise, enhancing muscle strength and recovery [ 143 ]. Controversial results come from these studies, sometimes yielding no effects of arginine supplementation on muscle performance, and sometimes demonstrating a significant improvement in exercise capability [ 137 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Arginine and No Production In Physiological Conditions: Tmentioning
confidence: 99%
“…For instance, arginine supplementation has been tested in athletes, as vasodilation favors muscle perfusion and nutrient/oxygen delivery during exercise, enhancing muscle strength and recovery [ 143 ]. Controversial results come from these studies, sometimes yielding no effects of arginine supplementation on muscle performance, and sometimes demonstrating a significant improvement in exercise capability [ 137 , 144 , 145 , 146 , 147 , 148 ].…”
Section: Arginine and No Production In Physiological Conditions: Tmentioning
confidence: 99%
“…Most similarly, Alvares et al reported that Larginine increased blood volume at the level of the muscle but failed to enhance muscular strength or endurance after ingestion of a sixgram dose of L-arginine 31 . The lack of efficacy is not supportive of an ergogenic effect after exogenous L-arginine ingestion [32][33][34] . As these suggest, muscular power, muscular endurance, or recovery are not increased with L-arginine supplementation.…”
Section: Discussionmentioning
confidence: 90%
“…Puga et al evaluated the effects of arginine supplementation on postmenopausal women who perform aerobic exercise and found a significant decrease in diastolic blood pressure values, while no beneficial changes were noted in cardio-inflammatory markers [ 35 ]. However, Andrade et al reported a non-significant effect in terms of muscle improvement of I-arginine supplementations after high-resistance exercise [ 36 ].…”
Section: Discussionmentioning
confidence: 99%